Arsitektur Akad Fintech Syariah: Pengembangan Kerangka Standarisasi Berbasis Konvergensi Fiqh, Fatwa, dan Putusan Pengadilan - Yasardin Yasardin; Amelia Rahmaniah; Avisena Ilma Rachmasari (Universitas Islam Negeri Antasari Banjarmasin, 2025)
The rapid expansion of Buy Now Pay Later (BNPL) schemes represents a major shift in consumer finance and has entered Islamic financial markets with significant controversy. While promoted as an inclusive financing solution, Islamic BNPL raises urgent concerns regarding hybrid contracts, Shariah compliance, and consumer protection. This trend reflects both technological change and a regulatory gap that demands systematic assessment and normative solutions.Existing studies on Islamic fintech largely focus on compliance checklists or technical contracts, leaving unresolved tensions between innovation, governance, and maqāṣid al-sharīʿah. This research addresses the problem of whether Islamic BNPL can be structured as a Shariah-compliant instrument that also supports economic democratization. Using doctrinal and normative legal analysis, this study examines Islamic BNPL practices through the lenses of Shariah governance, contract theory, and Islamic economic principles. The analysis reveals that loosely structured hybrid contracts often generate legal ambiguity, misallocate risk, and weaken ethical safeguards. Conversely, BNPL models grounded in clear contractual separation and effective Shariah oversight show stronger alignment with justice and inclusivity. This study concludes that Islamic BNPL requires governance reform rather than mere contractual labeling. It recommends regulatory harmonization, strengthened Shariah supervision, and contract standardization to ensure that BNPL contributes to responsible financial access and equitable economic development.